Shariah screening methodology / Hamizah Hassan and Nor Suhaira Jamil - Hassan, Hamizah; Jamil, Nor Suhaira (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Shariah-compliant securities are among the earliest Islamic Capital Market products available in Malaysia and were initially introduced to meet the demands of domestic institutional and retail investors for Shariah-compliant investments. The Shariah Advisory Council (SAC) of the Securities Commission has developed a methodology for screening the Shariah status of securities listed on the stock exchange. The screening process for Shariah compliance, leads to the issuance of the Shariah-compliant list in May and November each year which provides certainty and clarity on the status of securities listed on the stock exchange and has encouraged greater investor participation in the Islamic equity market.